SC6 Development of a dedicated SimTech workspace…… CPD and all that!. (3rd November 2019) - Nicklin, Jane; Clark, Alex
Abstract : Background: The Simulation Technician Education Programme (STEP) developed collaboratively with ASPiH and Laerdal Medical UK wanted to offer additional support to simulation technicians to not only prepare their competence report application for professional registration with the Science Council but also record and review their continual professional development (CPD). 1 iRIS, a collaborative, web-based simulation authoring platform developed by TWME8, a UK based software company, can already be accessed through one of the benefits of ASPiH membership and was therefore approached to develop a 'SimTech workspace' on their existing platform. 2 Summary of education programme or project: The space was developed to support technician's development, Science Council professional registration application and renewal alongside recording of their CPD. It is a resource to help prepare and refine competence reports and gain online support from an in-house Manager or an external Mentor It also helps technicians to better manage and record their professional development activities over time, annual appraisal and CPD evidence for professional registration renewal. Most importantly, it is a safe place for documents, professional development logs and any conversations with your Manager or chosen Mentor. Summary of results, benefits: Although still in its infancy, those accessing the 'workspace' are already seeing the benefits from the customised, dedicated area. It is personal, private, readily accessible and safe. Individuals have complete control of the resource re sharing with Mentors, line managers etc. It is a one-stop shop for recording activity and uploading evidence, documents etc. Conclusions and recommendations: In the future, technicians could opt to use iRIS's original functionality for scenario development and wider communications through the discussions/forum but for now it is hoped that Technicians will use the resource to support their professional development, whilst contributing to and improving the effectiveness and efficiency of their role. References: Simulation Technician Education Programme (STEP)https://2amcvm41x4633mbne5290mum-wpengine.netdna-ssl.com/wp-content/uploads/2019/04/STEP-Programme-Brief.2019.pdf (Accessed 31/05/19) iRIShttp://irissimulationauthoring.com/(Accessed 31/05/19)